Statistics : - Peck, Roxy (Thomson Brooks/Cole, 2008)
Our book can be used in course as short as one quater or as long as one year in duration. Particularly in shorter courses, an instructor will need to be selective in deciding which topics to include and which to set aside. The book divides naturally into four major sections: collecting data and descriptive methods (Chapter 1-5), probability material (Chapter 6-8), the basic one- and two-sample inferential methodology (Chapter 13-16).